Palaeomagnetic results from late Cretaceous and early Tertiary limestones from Tingri area, southern Tibet, China - Appel, E.; Li, H.; Patzelt, A.; Wang, J. (Journal of Nepal Geological Society, 1998)
Palaeomagnetic studies have been carried out on the late Campanian (Zhepure Shanbei Formation: ZSbF), early Palaeocene (Zbepure Shanpo Formation: ZSpF) and early to mid-Eocene (Zhepure Shan Formation, memberV: ZSFmV) limestones from the Tethyan Himalaya west of Tingri (28°48'N, 86°54'E) in southern Tibet (China). A primary component in the ZSbF is proven by normal and reverse polarity zones in a stratigraphic succession of uniform layers (1 site, 24 specimens). The inclination (-50.2°) approximately fits to the expected palaeolatitude of the area for late Campanian. However, this result bas to be considered with caution because of non-antipodal remanence directions. The ZSpF shows a recent field direction only and is affected by gyroremanence acquisition. In contrast to results published earlier by Besse et al. (1984), no primary component could be identified in the ZSFmV. The characteristic remanence (ChRM) isolated in this unit (5 sites, 32 specimens) is most likely of secondary origin. The significance of the fold test is below the 95% level due to rather uniform bedding attitudes, but tilt corrected inclinations are unrealistically high for the area. The polarity of the ChRM is reverse and thus represents a palaeoremanence acquired sometimes between the Brunbes/Matuyama boundary and Eocene times. Declinations of Besse et al. (1984)'s primary direction and of our secondary component in the ZSFmV coincide and suggest that no rotation of the Tingri area occurred between Eocene and the time where the remanence was acquired.